Inhibition of Heat Shock Protein 90 by 17-AAG Reduces Inflammation via P2X7 Receptor/NLRP3 Inflammasome Pathway and Increases Neurogenesis After Subarachnoid Hemorrhage in Mice - Zuo, Yuchun; Wang, Jikai; Liao, Fan; Yan, Xiaoxin; Li, Jianming; Huang, Lei; Liu, Fei (Frontiers in Molecular Neuroscience, 2018)
Subarachnoid hemorrhage (SAH) is a life-threatening cerebrovascular disease that usually has a poor prognosis. Heat shock proteins (HSPs) have been implicated in the mechanisms of SAH-associated damage, including increased inflammation and reduced neurogenesis. The aim of this study was to investigate the effects of HSP90 inhibition on inflammation and neurogenesis in a mouse model of experimental SAH induced by endovascular surgery. Western blotting showed HSP90 levels to be decreased, while neurogenesis, evaluated by 5-bromo-2'-deoxyuridine (BrdU) immunohistochemistry, was decreased in the hippocampuses of SAH mice. SAH also induced pro-inflammatory factors such as interleukin-1β (IL-1β), capase-1, and the NLRP3 inflammasome. However, intraperitoneal administration of the specific HSP90 inhibitor 17-allylamino-17-demethoxygeldanamycin (17-AAG) reduced the levels of HSP90, NLRP3, ASC, caspase-1, and IL-1β, while increasing the levels of brain-derived neurotrophic factor and doublecortin, as well as the number of BrdU-positive cells in SAH mice. In addition, 17-AGG improved short- and long-term neurobehavioral outcomes. The neuroprotective and anti-inflammatory effects of 17-AGG were reversed by recombinant HSP90; this detrimental effect of HSP90 was inhibited by the specific P2X7 receptor (P2X7R) inhibitor A438079, indicating that SAH-induced inflammation and inhibition of neurogenesis were likely mediated by HSP90 and the P2X7R/NLRP3 inflammasome pathway. HSP90 inhibition by 17-AAG may be a promising therapeutic strategy for the treatment of SAH.